Channel Capacity of High Altitude Platform Systems employing Non-Coherent Detection - Nguyen, Thu Hien; Nguyen, Viet Hung; Vu, Van San (Old Journal, 2017)
In this paper, we present the results of calculating the Differential Discrete-input Continuous-output Memoryless Channel (D-DCMC) capacity for the High Altitude Platform (HAP) systems using extrinsic information transfer (EXIT) chart tool. Influencing factors of the propagation environment such as free space loss, attenuation due to meteorological effects, and multipath fading are also taken into consideration in modelling HAP transmission channel. Furthermore, in order to benchmark the near-capacity channel code design, we compute the outage capacity of D-DCMC for HAP systems.